The economic burden of diarrhea in children under 5 years in Bangladesh - Hasan, MZ; Mehdi, GG; De Broucker, G; Ahmed, S; Ali, MW; Martin Del Campo, J; Constenla, D; Patenaude, B; Uddin, MJ (Elsevier, 2021)
Background: Diarrhea is a leading cause of morbidity and mortality among under-five children in Bangladesh. Hospitalization for diarrhea can pose a significant burden on households and health systems. The aim of this study was to estimate the cost of illness due to diarrhea from the healthcare facility, caregiver, and societal perspectives in Bangladesh.